Youla–Kucera based multi-objective car following controller. (October 2021) - Mahtout, I.; Navas, F.; Gonzalez, D.; Milanés, V.; Nashashibi, F.
Abstract: This paper presents the design and implementation of a novel multi-objective Adaptive Cruise Controller (ACC). The proposed control strategy is based on Youla–Kucera parametrization to interpolate two ACC controllers with conflicting objectives: (1) a performant controller with fast preceding tracking capabilities; and (2) a robust controller with perception noise attenuation capabilities within the system bandwidth. The proposed multi-controller structure uses tools of both performance and robust control in order to adapt car-following behavior to perception system status. The solution is implemented in an automated Renault ZOE, and compared to H ∞ controller, providing encouraging results.